RESIDUAL STRESS IN TI6AL4V OBJECTS PRODUCED BY DIRECT METAL LASER SINTERING - van Zyl, Ian; Yadroitsava, Ina; Yadroitsev, Igor (The South African Journal of Industrial Engineering, 2016)
Direct Metal Laser Sintering produces 3D objects using a layer-by- layer method in which powder is deposited in thin layers. Laser beam scans over the powder fusing powder particles as well as the previous layer. High-concentration of laser energy input leads to high thermal gradients which induce residual stress within the as- built parts. Ti6Al4V (ELI) samples have been manufactured by EOSINT M280 system at prescribed by EOS process-parameters. Residual stresses were measured by XRD method. Microstructure, values and directions of principal stresses inTi6Al4V DMLS samples were analysed.